Economic aspects of the energy crisis - Richardson, Harry W. (Lexington, Massachusetts : Lexington Books/Saxon House, 1975)
The intention of this book is to analyze the major issues arising from "energy crisis" that has dominated much of the discussion on United States economic policies since 1973. The book attempts to achieve three aims. First, the discussion is intended to be broad enough to provide a sufficiently deep background understanding of the major energy problems facing the United States now and in the future. Second, several recent large-scale studies of the energy situation that are too indigestible to be read by the non-specialist at summarized and evaluated. Third, the book leads up to an assessment of the appropriate scope and content of national energy policy.
Includes index.
Includes bibliographical references: p. 215-224.
ne 25/04/2018
Loans
Keywords: Power resources; Energy policy